Upaya Sekolah Sehat Bebas Anemia Di Desa Bone Kecamatan Nekamese Tahun 2023 - Novian A Yudhaswara; Karol Octrisdey; Kuntum E N; Agnes Rantesalu; Marni Tangkelangi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Adolescent nutritional problems are a continuation of childhood nutritional problems such as iron deficiency anemia. Prolonged iron deficiency can cause anemia. Teenagers need more to replace iron lost along with menstrual blood. Anemia in adolescent girls is currently still high, according to WHO, the world prevalence of anemia ranges from 40-88%. The majority of students at SMP Negeri 5 Nekamese are young women who are vulnerable to suffering from anemia, so it is necessary to conduct anemia education and measure hemoglobin (Hb) in young women. The aim of this community service is to increase the knowledge of young women about anemia and school health so that it becomes a healthy and anemia-free school. The empowerment method in this community service activity uses the Question and Answer Lecture method. Counseling was conducted for young women in grades 7, 8 and 9 at SMP Negeri 5 Nekamese on September 9 2023, which was attended by 30 young women. The activity began with preparations for making an examination stand, distributing leaflets, explaining material or counseling using the lecture method of question and answer and evaluation. Before the counseling is carried out, a pre-test is carried out, then after the counseling a post-test is carried out. The implication of this community service activity is an increase in young women's knowledge about anemia and healthy schools. It is hoped that after carrying out this activity, young women can prevent anemia during adolescence by increasing their food consumption patterns to be diverse, nutritious, balanced and safe.